Implementasi Mazmur 57:8 dalam Meningkatkan Komitmen Pemuda terhadap Paduan Suara di GPI Sidang Perumnas - Ribka Cristine Sitorus; Sarah Melis Siahaan; Sona Simbolon; Novita Aditya Manalu (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to examine the implementation of Psalm 57:8 in enhancing young peopleâ€™s commitment to choir ministry at GPI Sidang Perumnas. Psalm 57:8 emphasizes the importance of a â€œwilling heartâ€ as the foundation for praising and serving God. However, in reality, there remains a low level of commitment among youth in the choir ministry, characterized by a lack of discipline, responsibility, and consistency in attending rehearsals and ministry activities.This study employs a qualitative method with a descriptive approach, utilizing techniques such as observation, interviews, documentation, and literature review. The results of the study indicate that young peopleâ€™s commitment is significantly influenced by a readiness of heart that arises from ongoing spiritual formation. Additionally, other supporting factors include the development of discipline, a sense of community, leadership by example, as well as regular evaluation and motivation. Thus, the implementation of the value of a â€œwilling heartâ€ in Psalm 57:8 has been proven to enhance youth commitment in choir ministry, enabling them to serve with full responsibility, faithfulness, and joy. Keywords: willing heart, youth commitment, choir, church ministry, Psalm 57:8